The Secular Evolution of Planetary Nebula IC 418 and Its Implications for Carbon Star Formation - Albert A. Zijlstra; Quentin A. Parker (The Astrophysical Journal Letters)
The rate of stellar evolution can rarely be measured in real time. The fastest evolution (excluding event-driven evolution), where stars may evolve measurably over decades, is during the post–Asymptotic Giant Branch (AGB) phase. In this Letter we provide direct evidence for such a case. A secular, linear, factor of ∼2.5 increase is found in the strength of the [O iii ] lines relative to H β over an 130 yr period in the young, well-known, low-excitation planetary nebula IC 418. The increase is caused by the rising temperature of the central star. We use photoionization models to derive a model-dependent heating rate for the central star in the range 15–42 K yr ^−1 . These derived heating rates are very sensitive to the stellar mass, and yield a central-star mass of ∼0.560–0.583 M _⊙ . Initial–final mass relations based on the Miller–Bertolami models give a progenitor main-sequence mass of 1.25–1.55 M _⊙ . IC 418 is a carbon-rich planetary nebula and its central star, HD 35914, has evolved from an AGB carbon star. This result shows that carbon star formation at solar metallicity extends to these low masses. This is lower than commonly assumed and suggests that post-AGB evolution may be slower than recent post-AGB models predict.